HYPERTEXT BASED INTERACTIVE MULTIMEDIA DEVELOPMENT - Fajriani, Alfiah; Darman, Darman; Saputra, Hendra Nelva; Sinarti, Andi (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2020)
AbstractThis research is based on the need to design learning media that can make students can interact with learning media, can be used easily, and can be used at any time in biology learning. The purpose of this research is to create biology learning media in the form of interactive multimedia based on hypertext that is feasible for use in learning. The research method used in this research is Lee & Owens development model which consists of 4 steps namely analysis, design, implemnetation and development, and evaluation. The resulting development product is interactive multimedia. Based on the description of the results and discussions, it can be concluded that hypertext-based interactive multimedia is categorized as very feasible with an average validity percentage of media experts of 83.3%, material experts of 88.19%, and students of 95.83%. These results show that hypertext-based interactive multimedia developed is very feasible to be used in biology learning, believed to facilitate the achievement of learning objectives, increase interest, motivation, mastery of concepts, and student learning outcomes. Keywords: Biology, Hypertext, Interactive MultimediaDOI: http://dx.doi.org/10.23960/jpvti.v2.i2.202004